2017
DOI: 10.1021/acs.jpcc.6b12970
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Reclaimed Electrolytes from Spent Lithium-Ion Batteries

Abstract: As an indispensable part of lithium-ion batteries (LIBs), closed-loop recycling, reusing the electrolyte from spent LIBs, has not yet been fulfilled experimentally. Herein, this paper presents a LIB electrolyte recycling approach which consists of supercritical CO2 extraction, resin, and molecular sieve purification and components supplements. The resultant electrolyte exhibited a high ionic conductivity of 0.19 mS·cm–1 at 20 °C, which was very close to a commercial electrolyte with the same composition. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 48 publications
0
64
0
Order By: Relevance
“…Currently, the main electrolyte recycling methods are classified as vacuum pyrolysis, organic solvent extraction, and supercritical CO 2 extraction 23 . Referring to a previous work by Liu et al, high-efficiency recycling of the electrolyte has been demonstrated, and the recycled electrolyte can be reused in new batteries 16,24 . Second, the recycling of metallic anodes is also highly feasible.…”
Section: Discussionmentioning
confidence: 84%
“…Currently, the main electrolyte recycling methods are classified as vacuum pyrolysis, organic solvent extraction, and supercritical CO 2 extraction 23 . Referring to a previous work by Liu et al, high-efficiency recycling of the electrolyte has been demonstrated, and the recycled electrolyte can be reused in new batteries 16,24 . Second, the recycling of metallic anodes is also highly feasible.…”
Section: Discussionmentioning
confidence: 84%
“…Recycling the electrolyte of LIBs is a critical concern. Liu et al [273] reported a method based in a supercritical CO2 extraction, resin, and molecular sieve purification, can contribute to producing a regenerated high ionic conductivity electrolyte, almost close to the commercial ones. Figure 20 represents the steps involved in this proposed method, which are supercritical CO2 extraction to separate the electrolyte, followed by its collection and purification in a glovebox under argon atmosphere.…”
Section: Separator/electrolytementioning
confidence: 99%
“…Given the enormous amounts of CO 2 generated in industry and progress in carbon capture strategies, the application of supercritical CO 2 for electrolyte recovery may thus be combined toward an integrative sustainable system. Liu et al [184] studied the purification and subsequent characterization of recycled electrolytes, which were extracted using supercritical CO 2 . Followed by purification with resins and molecular sieves, the reclaimed electrolyte achieved a high ionic conductivity of 0.19 mS cm −1 ; a value close to commercially available electrolytes for LIBs.…”
Section: Electrolytementioning
confidence: 99%